Pengaruh Lingkungan Kerja dan Disiplin Kerja Serta Kelelahan Kerja terhadap Kinerja Pegawai Kantor BPSDM Kaltim - Riyan Sawal Maulana; Yohanes Kuleh (Indo Publishing, 2026)
This study aims to analyze the influence of work environment, work discipline, and work fatigue on employee performance at the BPSDM Kaltim office. This research employed a quantitative approach with a sample of 68 respondents selected using proportional random sampling. Data were collected through questionnaires and analyzed using multiple linear regression analysis with SPSS software. The results indicate that the work environment has no significant effect on employee performance (p = 0.986 > 0.05). Work discipline has a positive and significant effect on employee performance (p = 0.000 < 0.05). Work fatigue has no significant effect on employee performance (p = 0.195 > 0.05). Simultaneously, work environment, work discipline, and work fatigue have a significant effect on employee performance (F = 5.895; p = 0.001). The coefficient of determination (R²) of 0.217 indicates that the three variables are only able to explain 21.7% of the variation in employee performance, while the remaining 78.3% is influenced by other factors outside this study. The findings of this study indicate that work discipline is the most dominant factor influencing employee performance at the BPSDM Kaltim office. Employees with high work discipline, such as arriving on time, complying with regulations, working according to procedures, and having responsibility, are proven to be able to improve their performance quality